Psychiana man : a mail-order prophet, his followers, and the power of belief in hard times - Schrand, Brandon R. (Washington State University Press, 2021)
"Psychiana creator and mass-marketing genius Frank Bruce Robinson's biography traces the flamboyant false prophet's improbable rise and fall during the Great Depression. The voices of his unwavering followers-from a desperate dust bowl farmer to a former heavyweight boxing champion-paint an intriguing, intimate view of the power of belief"--